Polish deputies support to the anti-vaccination movement in social media. The case of Confederation leaders - Skrzypek, Maciej (Springer, 2023)
The coronavirus crisis showed that politicians may use their official fan pages in social media to spread misleading information promoted by anti-vaccination movements. The research analyses the phenomenon taking into account the accountability of deputies as representatives of the nation. To verify the research hypothesis, I choose cases of two Confederation’s (Konfederacja) deputies, and formulate the following questions: How followers of fake news about COVID-19 vaccines use deputies’ profiles to promote such content? What is the motivations behind the phenomenon? and Who was involved in sharing fake news? Based on the questions, I formulated a hypothesis that anti-vaccination information is spread by some Polish deputies using their profiles in social media. Fake news about COVID-19 vaccines have been disseminated by publishing on social media profiles and using comments to posted by users. Further in the article, I refer to essential papers discussing the use of social media to spreading misinformation about COVID-19 and vaccines. This explains the purpose of selecting sources and cases analysed. The article finally shows results of my quantitative and qualitative analysis of the sources. Comparative studies draw on qualitative and quantitative analyses of two types of social media content, i.e. posts on Facebook and users' comments during the first half-year of mass vaccination. The selection of sources is based on the following criteria: Konfederacja deputies were the only in the Polish Parliament who manifested their doubts about COVID-19 vaccination. The caesura started on December 26, 2020 with the beginning of the vaccination program in Poland. It ends on June 26, 2021, with the end of the first half-year of vaccination, when the government started mass vaccination for all adults in Poland.
Jest to manuskrypt publikacji, która ukazała się w książce: Musiał-Karg Magdalena, Luengo Óscar G. (red.): Digital Communication and Populism in Times of Covid-19. Cases, Strategies, Examples, Studies in Digital Politics and Governance, 2023, Cham, Springer, 207 s., ISBN 9783031337154. DOI: https://doi.org/10.1007/978-3-031-33716-1_8).
Keywords: anti-vaccination movements; Konfederacja; Polish political parties; anti-vaccination content; COVID-19